Fuel cell unit cell
The implementation of a polyvinyl butyral-based adhesive layer addresses adhesion and heat resistance issues in fuel cell unit cells, ensuring stable bonding and efficient production.
Patent Information
- Application Number
- JP2021174813
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-10-26
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2041-10-26
AI Technical Summary
Conventional fuel cell unit cells face issues with adhesives used to bond the membrane electrode assembly (MEA) and support frame, such as catalyst poisoning due to volatile components and adhesion loss under hydrothermal conditions, leading to decreased adhesion, heat resistance, and productivity.
Employing a hot melt adhesive layer containing polyvinyl butyral as the main ingredient to bond the MEA and support frame, which provides improved adhesion, heat resistance, and productivity.
The use of polyvinyl butyral adhesive layer enhances adhesion, maintains catalyst integrity, and improves the thermal stability and manufacturing efficiency of fuel cell unit cells.
Smart Images

Figure 0007609031000004 
Figure 0007609031000001 
Figure 0007609031000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a unit cell of a fuel cell. [Background technology]
[0002] A fuel cell is constructed by stacking a plurality of membrane electrode assemblies (hereinafter also referred to as "MEA"), each of which is made up of an electrolyte membrane and an anode-side and cathode-side electrode catalyst layer sandwiching the electrolyte membrane, with separators interposed between them. Gas diffusion layers (hereinafter also referred to as "GDL") are arranged on both sides of the MEA to provide a fuel gas or an oxidant gas and to collect electricity generated by an electrochemical reaction. The MEA with the GDLs arranged on both sides may be referred to as a membrane electrode and gas diffusion layer assembly (hereinafter also referred to as "MEGA"). The MEGA is sandwiched between a pair of separators. The MEA or MEGA is also referred to as a fuel cell unit cell, a fuel cell cell, or a single cell.
[0003] Because the MEGA is thin and easily bent, for example, MEGAs having a configuration in which a support frame that supports the MEGA is arranged on the outer periphery of the MEGA (hereinafter also referred to as a "frame MEGA") are known for the purpose of protecting the MEGA or reducing manufacturing costs. A fuel cell unit cell having a frame MEGA configuration is usually manufactured by bonding the MEGA and the support frame with an adhesive.
[0004] For example, Patent Document 1 describes a method for manufacturing a fuel cell including a membrane electrode assembly in which an electrode catalyst layer is formed on each side of an electrolyte membrane, gas diffusion layers disposed on each side of the membrane electrode assembly, and a support frame formed of a thermoplastic resin and supporting the membrane electrode assembly on the outer periphery of the membrane electrode assembly, the method including the steps of: preparing the membrane electrode assembly in which a gas diffusion layer is disposed on one side of the membrane electrode assembly and no gas diffusion layer is disposed on the other side of the membrane electrode assembly; forming an adhesive layer made of a radical polymerization type ultraviolet-curable adhesive on the outer periphery of the other side of the membrane electrode assembly; and irradiating the adhesive layer with ultraviolet light while closely adhering a cooling plate that prevents a temperature rise of the support frame to the support frame, and bonding the membrane electrode assembly and the support frame via the adhesive layer irradiated with ultraviolet light. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2019-096389 A Summary of the Invention [Problem to be solved by the invention]
[0006] As described above, a fuel cell unit cell having a support frame has been developed. However, there are some problems with the conventional fuel cell unit cells. For example, when a liquid adhesive is used as an adhesive for bonding the MEGA and the support frame, the adhesive has sufficient adhesion, but the heat generated during the operation of the fuel cell may cause the volatile components in the adhesive to react with the catalytic metal (e.g., platinum) in the electrode catalyst layer to generate decomposition gas. The decomposition gas generated by such a reaction may poison the catalytic metal and cause a decrease in the output of the fuel cell. In addition, when a solid adhesive (e.g., a hot melt adhesive) is used, the above problems can be avoided, but in the environment inside the fuel cell unit cell during operation of the fuel cell, for example, in a hydrothermal environment, the adhesive may decrease in adhesion and the adhesive may easily peel off from the electrolyte membrane. If these problems occur, the adhesiveness, heat resistance and / or productivity of the fuel cell unit cell may decrease as a result.
[0007] Therefore, an object of the present invention is to provide a fuel cell unit cell having an adhesive layer that combines adhesiveness, heat resistance and / or productivity. [Means for solving the problem]
[0008] The present inventors have investigated various means for solving the above problems. The present inventors have found that by using polyvinyl butyral as the main agent of the adhesive, a fuel cell unit cell having an adhesive layer that combines adhesiveness, heat resistance, and / or productivity can be obtained. Based on the above findings, the present inventors have completed the present invention.
[0009] That is, the present invention includes the following aspects and embodiments. (1) a membrane electrode assembly having an electrolyte membrane and a pair of electrode catalyst layers laminated on both sides of the electrolyte membrane; A support frame for supporting the membrane electrode assembly; an adhesive layer that bonds the membrane electrode assembly and the support frame; A fuel cell unit cell comprising: the electrode catalyst layer is laminated on an inside of an outer peripheral side surface of the electrolyte membrane on at least one surface of the membrane electrode assembly, and the adhesive layer is arranged so as to bond the outer peripheral side surface of the electrolyte membrane and the support frame to each other; The adhesive layer is a hot melt adhesive layer containing polyvinyl butyral. The fuel cell unit cell. Effect of the Invention
[0010] According to the present invention, it is possible to provide a fuel cell unit cell having an adhesive layer that combines adhesiveness, heat resistance and / or productivity. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a cross-sectional view showing an embodiment of a unit cell of a fuel cell according to an aspect of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Preferred embodiments of the present invention will now be described in detail.
[0013] <1. Fuel cell unit cell> The present inventors have found that, in a fuel cell unit cell having a support frame, by using polyvinyl butyral as a main agent of an adhesive that bonds a membrane electrode assembly and a support frame, it is possible to obtain a fuel cell unit cell having an adhesive layer that combines adhesiveness, heat resistance, and / or productivity. Therefore, one aspect of the present invention relates to a fuel cell unit cell.
[0014] A cross-sectional view showing one embodiment of a fuel cell unit cell of this aspect is shown in Fig. 1. As shown in Fig. 1, a fuel cell unit cell 10 includes a membrane electrode assembly 1 having an electrolyte membrane 4 and a pair of electrode catalyst layers 5 laminated on both sides of the electrolyte membrane 4, a support frame 2 supporting the membrane electrode assembly 1, and an adhesive layer 3 bonding the membrane electrode assembly 1 to the support frame 2. One of the pair of electrode catalyst layers 5 is an anode-side electrode catalyst layer, and the other is a cathode-side electrode catalyst layer.
[0015] In the fuel cell unit cell 10, on at least one surface of the membrane electrode assembly 1, the electrode catalyst layer 5 is laminated on the inside of the outer peripheral side surface of the electrolyte membrane 4. For example, on one surface of the membrane electrode assembly 1, the electrode catalyst layer 5 may be laminated on the inside of the outer peripheral side surface of the electrolyte membrane 4, and on the other surface, the electrode catalyst layer 5 may be laminated so as to extend over the entire outer peripheral side surface of the electrolyte membrane 4. Alternatively, on both surfaces of the membrane electrode assembly, the electrode catalyst layer may be laminated on the inside of the outer peripheral side surface of the electrolyte membrane.
[0016] In the fuel cell unit cell 10, the adhesive layer 3 is disposed so as to bond the outer peripheral side surface of the electrolyte membrane 4 and the support frame 2 to each other. For example, when the electrode catalyst layer 5 is laminated on the inside of the outer peripheral side surface of the electrolyte membrane 4 on one surface of the membrane electrode assembly 1, the adhesive layer 3 can be disposed so as to bond the outer peripheral side surface of the electrolyte membrane 4 on that one surface and the support frame 2 to each other, and the electrode catalyst layer 5 can be laminated on the other surface so as to extend over the entire outer peripheral side surface of the electrolyte membrane 4. Alternatively, the electrode catalyst layer may be laminated on the inside of the outer peripheral side surface of the electrolyte membrane on the other surface as well.
[0017] In the fuel cell unit cell 10, the specific arrangement of the support frame 2 is not particularly limited as long as it is adhered to the outer peripheral side surface of the electrolyte membrane 4 via the adhesive layer 3. For example, as shown in Fig. 1, the support frame 2 may be arranged on the outer periphery of the membrane electrode assembly 1 so as to be spaced apart from the membrane electrode assembly 1. Alternatively, the support frame may be arranged on the outer periphery of the membrane electrode assembly so as to abut against the membrane electrode assembly.
[0018] The fuel cell unit cell of this embodiment may further include any member applied to a fuel cell unit cell, such as a gas diffusion layer and a separator. For example, as shown in FIG. 1, in one embodiment, a fuel cell unit cell 10 may include a pair of gas diffusion layers 6 laminated on the outer peripheral side surface of the electrode catalyst layer 5, and a pair of separators 7 arranged on the outer peripheral side surface of the gas diffusion layers 6. In this embodiment, the fuel cell unit cell 10 may further include a gas flow path 8 defined by the gas diffusion layer 6 and the separator 7. An oxidizing gas flows through the gas flow path defined by the gas diffusion layer and the separator arranged on the cathode electrode catalyst layer side, and a fuel gas flows through the gas flow path defined by the gas diffusion layer and the separator arranged on the anode electrode catalyst layer side. With this configuration, an electrochemical reaction proceeds in the membrane electrode assembly to generate an electromotive force.
[0019] In the fuel cell unit cell of this embodiment, the adhesive layer contains polyvinyl butyral. In this case, polyvinyl butyral is contained in the adhesive layer as a main component. That is, the adhesive layer in the fuel cell unit cell of this embodiment is a hot melt adhesive layer. The adhesive layer having the above characteristics can substantially avoid the poisoning of the catalyst metal due to heat and the decrease in the output of the fuel cell, which may occur when using a liquid adhesive. In addition, as shown in the following examples, the adhesive layer containing polyvinyl butyral has high adhesion, and is also high in heat resistance and productivity compared to adhesive layers containing known materials such as ethylene-vinyl alcohol copolymer (hereinafter also referred to as "EVOH") and polyamide as main components. Therefore, by using an adhesive layer containing polyvinyl butyral, a fuel cell unit cell having an adhesive layer that combines adhesion, heat resistance, and / or productivity can be obtained.
[0020] In each aspect of the present invention, the adhesion of the adhesive layer can be evaluated, for example, by subjecting a test piece prepared using the adhesive layer to a tensile test under specified conditions and observing the occurrence of breakage, peeling, etc.
[0021] In each embodiment of the present invention, the heat resistance of the adhesive layer can be evaluated, for example, by using the melting point of the material (e.g., the base material) contained in the adhesive layer as an index. The melting point of the material (e.g., the base material) contained in the adhesive layer can be measured, for example, by a differential scanning calorimeter.
[0022] In each embodiment of the present invention, the productivity of the adhesive layer can be evaluated, for example, using the glass transition temperature of the material (e.g., the base material) contained in the adhesive layer as an index. The glass transition temperature of the material (e.g., the base material) contained in the adhesive layer can be measured, for example, by a differential scanning calorimeter.
[0023] The polyvinyl butyral contained in the adhesive layer preferably has the repeating structure shown below.
[0024] [ka]
[0025] In the above formula, m is the butyral group ratio (mol%), n is the hydroxyl group ratio (mol%), and l is the acetyl group ratio (mol%). m, n, and l are the ratios of the number of moles of each group to the total number of moles of the entire polyvinyl butyral polymer. The butyral group ratio (m) is preferably in the range of 50 to 60. The hydroxyl group ratio (n) is preferably in the range of 37 to 47. The acetyl group ratio (l) is preferably in the range of 1 to 4. By using an adhesive layer containing polyvinyl butyral having the above characteristics, it is possible to obtain a fuel cell unit cell having an adhesive layer that combines adhesiveness, heat resistance, and / or productivity.
[0026] In addition to the polyvinyl butyral described above, the adhesive layer may contain one or more additional components such as a rubber filler, a crosslinking agent, a plasticizer, a heat stabilizer, a hydrolysis inhibitor, and a compatibilizer.
[0027] The shape of the adhesive layer is not particularly limited, and may be any shape, such as a sheet. The adhesive layer may have a single layer structure or a multi-layer structure. When the adhesive layer is in a sheet shape, the thickness is usually in the range of 10 to 100 μm. In this case, the thickness of the adhesive layer is preferably 10 μm or more, more preferably 20 μm or more, even more preferably 30 μm or more, and particularly preferably 40 μm or more. The thickness of the adhesive layer is preferably 100 μm or less, more preferably 90 μm or less, even more preferably 70 μm or less, and particularly preferably 50 μm or less.
[0028] In the fuel cell unit cell of this embodiment, the electrolyte membrane can be formed from any material that is commonly used as an electrolyte layer in a fuel cell unit cell, such as a fluorine-based polymer having ion conductivity, for example, a proton-conducting ion exchange polymer having a perfluorosulfonic acid group (i.e., a perfluorosulfonic acid polymer).
[0029] In the fuel cell unit cell of this embodiment, the electrode catalyst layer can be formed of an electrode catalyst in which a catalytic metal is supported on a carrier.
[0030] The catalytic metal can be made of any material commonly used as an electrode catalyst in a fuel cell unit cell, such as Pt, Pd, Rh, and the like, and alloys containing one or more of these metals.
[0031] The support may be made of any material commonly used as an electrode catalyst layer in a fuel cell unit cell, such as carbon particles made of a carbon support such as glassy carbon, carbon black, activated carbon, coke, natural graphite, or artificial graphite.
[0032] In the fuel cell unit cell of this embodiment, the support frame can be formed of any material having electrical insulation and airtightness. Examples of such materials include thermosetting resins and thermoplastic resins. The material forming the support frame is preferably a thermoplastic resin such as polyethylene, polypropylene, cyclic polyolefin resin, polyphenylene ether resin, polyethylene naphthalate resin (PEN), polyetherimide, polyimide, polyphenylsulfone (PPS), polyethersulfone, polyphenylsulfone, or polysulfone.
[0033] In the fuel cell unit cell of this embodiment, the gas diffusion layer can be formed from any material that is commonly used as a gas diffusion layer for a fuel cell unit cell. Examples of such materials include conductive porous bodies. Examples of such porous bodies include carbon porous bodies such as carbon paper, carbon cloth, and glassy carbon, and metal porous bodies such as metal mesh and metal foam.
[0034] In the fuel cell unit cell of this embodiment, the separator can be formed from any material that is normally used as a separator for a fuel cell unit cell. Examples of such materials include gas-impermeable conductive materials. Examples of such gas-impermeable conductive materials include dense carbon made by compressing carbon to make it gas-impermeable, and press-molded metal plates.
[0035] <2. Manufacturing method of fuel cell unit cell> Another aspect of the present invention relates to a method for producing the fuel cell unit cell of the aspect of the present invention described above. The method of this aspect includes the steps of preparing a membrane electrode assembly having an electrolyte membrane and a pair of electrode catalyst layers laminated on both sides of the electrolyte membrane, preparing a support frame, preparing an adhesive layer, and bonding the membrane electrode assembly and the support frame via the adhesive layer.
[0036] In the method of this aspect, the step of preparing each member can be carried out by various methods known in the art using the materials of each member having the features described above.
[0037] In the manufacturing method of this aspect, the step of bonding the membrane electrode assembly and the support frame via an adhesive layer can be carried out by means such as hot pressing which is usually carried out in the art. In this case, the temperature of the hot pressing can be appropriately set based on the melting point of the polyvinyl butyral contained in the adhesive layer described above. The temperature of the hot pressing is preferably, for example, a temperature of 80°C or higher and less than the melting point of polyvinyl butyral.
[0038] As described in detail above, the fuel cell unit cell of one aspect of the present invention has high adhesiveness, heat resistance and / or productivity in the adhesive layer. Therefore, the fuel cell unit cell of one aspect of the present invention can be applied to, for example, fuel cells for automobiles, ships or railway vehicles.
Examples
[0039] Hereinafter, the present invention will be described more specifically using examples. However, the technical scope of the present invention is not limited to these examples.
[0040] <I: Manufacture of fuel cell unit cell> [I-1: Example 1] An electrolyte membrane (thickness 25 μm, Nafion (registered trademark), manufactured by DuPont) was cut into a rectangle of 10 mm in length × 30 mm in width to prepare an electrolyte membrane piece.
[0041] A polyvinyl butyral membrane (thickness 40 μm) having a butyral group ratio (m) of 55 mol%, a hydroxyl group ratio (n) of 42 mol%, and an acetyl group ratio (l) of 3 mol% was molded by extrusion molding. The obtained membrane was cut into a rectangle of 10 mm in length × 40 mm in width to prepare an adhesive layer piece for Example 1.
[0042]
Chemical formula
[0043] The electrolyte membrane piece and the adhesive layer piece were laminated so that the 10 mm x 10 mm portions of the longitudinal ends overlapped each other. The laminated portions were hot-pressed under conditions of 1 MPa, 100°C, and 1 minute. In this way, the laminated portions of the electrolyte membrane piece and the adhesive layer piece were thermocompression-bonded to prepare a test piece simulating a unit cell of a fuel cell.
[0044] [I-2: Comparative example 1] A film (thickness 40 μm) made of polyamide nylon 12 was molded by extrusion molding. The obtained film was cut into a rectangle of length 10 mm × width 40 mm to prepare an adhesive layer piece of Comparative Example 1. A test piece of Comparative Example 1 was prepared using the same materials and procedures as in Example 1, except that this adhesive layer piece was used.
[0045] [I-3: Comparative example 2] A film (thickness 40 μm) made of nylon 9, which is a polyamide, was molded by extrusion molding. The obtained film was cut into a rectangle of length 10 mm × width 40 mm to prepare an adhesive layer piece of Comparative Example 2. A test piece of Comparative Example 2 was prepared using the same materials and procedures as in Example 1, except that this adhesive layer piece was used.
[0046] [I-4: Comparative example 3] An ethylene-vinyl alcohol copolymer (EVOH) film (thickness 40 μm) with an ethylene ratio of 95 mol% was molded by a casting method. The obtained film was cut into a rectangle of 10 mm length x 40 mm width to prepare an adhesive layer piece of Comparative Example 3. A test piece of Comparative Example 3 was prepared using the same materials and procedures as in Example 1, except that this adhesive layer piece was used.
[0047] [I-5: Comparative example 4] A film (thickness 40 μm) made of nylon 6, which is a polyamide, was molded by extrusion molding. The obtained film was cut into a rectangle of length 10 mm × width 40 mm to prepare an adhesive layer piece of Comparative Example 4. A test piece of Comparative Example 4 was prepared using the same materials and procedures as in Example 1, except that this adhesive layer piece was used.
[0048] [I-6: Comparative Example 5] An ethylene-vinyl alcohol copolymer (EVOH) film (thickness: 40 μm) with an ethylene ratio of 38 mol% was molded by the casting method. The obtained film was cut into a rectangle of 10 mm in length and 40 mm in width to prepare an adhesive layer piece for Comparative Example 5. Test pieces for Comparative Example 5 were prepared using the same materials and procedures as in Example 1, except that this adhesive layer piece was used.
[0049] <II: Evaluation Test of Fuel Cell Unit Cells> [II-1: Evaluation of Adhesiveness] The test pieces of Example 1 and Comparative Examples 1 to 5 were respectively placed in vial bottles and immersed in hot water under the conditions of 95°C for 500 hours. Then, each test piece was cooled to 25°C. The adhesive layer pieces of each test piece were reinforced with Kapton tape. Each test piece was subjected to a tensile test under the conditions of 25°C and 10 mm / min. The tensile test was carried out until the electrolyte membrane piece broke or the electrolyte membrane piece and the adhesive layer piece peeled off.
[0050] [II-2: Evaluation of Heat Resistance] The melting points of the adhesive layer pieces of Example 1 and Comparative Examples 1 to 5 were measured by a differential scanning calorimeter.
[0051] [II-3: Evaluation of Productivity] The glass transition points of the adhesive layer pieces of Example 1 and Comparative Examples 1 to 5 were measured by a differential scanning calorimeter.
[0052] [II-4: Results of Evaluation Tests] The results of each evaluation test are shown in Table 1. In the table, the adhesiveness result of "○" indicates that the adhesive piece broke in the tensile test, and "×" indicates that the electrolyte membrane and the adhesive piece peeled off in the tensile test. The heat resistance result of "◎" indicates that the melting point was 200°C or higher, "○" indicates that the melting point was in the range of 150°C or higher and less than 200°C, and "×" indicates that the melting point was less than 150°C. In addition, the productivity result of "○" indicates that the glass transition point was less than 100°C, and "△" indicates that the glass transition point was 100°C or higher.
[0053] [Table 1]
[0054] The present invention is not limited to the above-described embodiments, but includes various modified examples. For example, the above-described embodiments have been described in detail to clearly explain the present invention, and the present invention is not necessarily limited to those including all of the configurations described. In addition, it is possible to add, delete, and / or replace part of the configuration of each embodiment with other configurations. [Explanation of symbols]
[0055] Reference Signs List 1... membrane electrode assembly, 2... support frame, 3... adhesive layer, 4... electrolyte membrane, 5... electrode catalyst layer, 6... gas diffusion layer, 7... separator, 8... gas flow path, 10... fuel cell unit cell
Claims
[Claim 1] a membrane electrode assembly having an electrolyte membrane and a pair of electrode catalyst layers laminated on both sides of the electrolyte membrane; A support frame for supporting the membrane electrode assembly; an adhesive layer that bonds the membrane electrode assembly and the support frame; A fuel cell unit cell comprising: the electrode catalyst layer is laminated on an inside of an outer peripheral side surface of the electrolyte membrane on at least one surface of the membrane electrode assembly, and the adhesive layer is arranged so as to bond the outer peripheral side surface of the electrolyte membrane and the support frame to each other; The adhesive layer is a hot melt adhesive layer containing polyvinyl butyral. The fuel cell unit cell.
Citation Information
Patent Citations
Preparation system and method of membrane electrode and fuel cell
CN107171008A
Fuel cell and manufacturing method of the same
JP2016012444A
Thermal adhesive film
JP2016056243A
Fuel battery single cell and manufacturing method for the same
JP2016162649A
Method of manufacturing fuel battery cell
JP2019096389A